2021
DOI: 10.1080/23311975.2021.1944008
|View full text |Cite
|
Sign up to set email alerts
|

The influence of social media on purchase intention: The mediating role of brand equity

Abstract: The paper examined the relationship between social media and purchase intention and the mediation role of brand equity within Ghana's fashion industry. The study was quantitative and employed the survey methodology to sample the views of 500 fashion customers. Statistical Package for Social Sciences (SPSS) and the structural equation modelling (SEM) technique were used using AMOS software version 22.0 to determine the hypothesized relationships of the study. The study findings revealed that surveillance, Infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
38
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 17 publications
6
38
1
3
Order By: Relevance
“…The findings of this study add to the existing digital advertising literature that SMM has a significant direct effect on PI: the effect of SMM is transferred to PI through CBBE and INS. Further, the results confirm that CBBE and INS lead to PI and are similar to the findings of previous studies (Izogo and Mpinganjira, 2020; Majeed et al , 2021; Sheng et al , 2020; Tang and Tsang, 2020). This study also attempted to assess the indirect effect of SMM on PI through CBBE and INS, which were proposed in H6 and H7 .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The findings of this study add to the existing digital advertising literature that SMM has a significant direct effect on PI: the effect of SMM is transferred to PI through CBBE and INS. Further, the results confirm that CBBE and INS lead to PI and are similar to the findings of previous studies (Izogo and Mpinganjira, 2020; Majeed et al , 2021; Sheng et al , 2020; Tang and Tsang, 2020). This study also attempted to assess the indirect effect of SMM on PI through CBBE and INS, which were proposed in H6 and H7 .…”
Section: Discussionsupporting
confidence: 91%
“…Many studies in the recent past have found a positive relationship between SMM and CBBE (Ebrahim, 2020;Godey et al, 2016;Seo and Park, 2018;Zollo et al, 2020) and between CBBE and PI (Beneke et al, 2016;Moreira et al, 2017). Very few studies (Majeed et al, 2021) have investigated the indirect effect of SMM on PI through CBBE, and hence this study adds to the existing literature by proposing the following hypothesis for investigation:…”
Section: Mediation Effect Of Consumer-based Brand Equity and Consumer...mentioning
confidence: 80%
See 2 more Smart Citations
“…However, the results of this study are unique due to the complexity of the theoretical framework. This study is also in line withMajeed et al (2021) who evaluated the effects of social media advertising on the consumer's purchase intentions along with the mediating role of brand equity in Ghana's fashion industry. This study is in line with the sense of social media advertising's influence on the purchase intentions of consumers in the fashion clothing sector.…”
supporting
confidence: 75%